Economic and environmental influence of metal recycling in the central sertão region of Pernambuco - Pessoa, Gênesis de Brito; Albuquerque, Carlos Eduardo da Silva (Brazilian Journal of Production Engineering, 2024)
Recycling solid materials plays a crucial role in sustainable waste management and environmental preservation. This process involves collecting, separating and processing discarded materials such as paper, plastic, glass and metal to create new products. Its advantages include reduced extraction of natural resources, less waste in landfills and less pollution. In addition, recycling contributes to the circular economy, promoting efficiency in the use of resources and encouraging more sustainable practices. This specific study focuses on the economic and environmental influence of metal recycling in the Central Sertão of Pernambuco, with an emphasis on the city of Salgueiro-PE. The research was conducted with a total of 18 professionals involved in the collection of recycled materials. The results show the positive impacts of metal recycling, highlighting significant improvements in both income and the local environment. In addition, the research identified challenges faced by these professionals, such as the low prices practiced on the market and the lack of incentives from the government. The conclusion of the study reinforces the urgency of implementing improvements in economic and environmental aspects, highlighting the crucial importance of recycling in fostering sustainable development in Salgueiro-PE.
Keywords: Economy; Environment; Metals; Recycling; Reuse